Efektivitas Flashcard Digital Sebagai Media Pedagogis dalam Pembelajaran Kosakata Bahasa Inggris: Systematic Literature Review - Al Faruq, Habibatul Azizah; Wardati, Nanda Kurnia; Abdillah, Firman Puji; Putri, Sayang Indriani (Politeknik Harapan Bersama, 2025)
Vocabulary mastery is a fundamental aspect in English language learning. However, vocabulary learning is often boring and less interactive, so students have difficulty remembering and understanding new words. Digital learning applications such as flashcards offer an innovative solution to overcome this obstacle by having interactive features that can improve students' memory and learning interest. This study aims to evaluate the effectiveness of using digital flashcard applications as a pedagogical medium for teaching English vocabulary. Although some findings state that flashcards are effective in improving vocabulary in learning activities, a systematic review of the existing literature is needed to assess the extent to which digital flashcard applications have an impact on vocabulary learning both in terms of improving learning outcomes, learning motivation, and other aspects related to pedagogy. This study uses the Systematic Literature Review (SLR) method by reviewing several journals discussing the research topic. The results of the study indicate that digital flashcards as a learning media strategy can be said to be effective in improving students' vocabulary mastery ranging from elementary school, MTs, vocational high schools, to undergraduate students, which in this case can enrich vocabulary; easy, easy to recognize images, words, and meanings; Students are more active, focused, and enthusiastic when learning English; improve receptive and productive aspects in vocabulary knowledge; remembering material easily; and increasing students' learning motivation.